IMPACT OF DIGITAL MARKETPLACES ON MICRO-ENTREPRENEURSHIP GROWTH IN ENUGU STATE (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Online markets have become an innovative avenue to micro-entrepreneurship, which allows small-scale business persons in Enugu State, Nigeria, to reach out to larger markets, lower operational expenses, and increase the business potential. Digital marketplaces, including Jumia, Konga, and social media, have the potential to fundamentally change the operations of micro-enterprises in Enugu and this article explores the role of digital marketplaces in increasing revenue, its customer base, as well as its efficiency in conducting business. Adopting primary data collection method comprising of surveys and interviews of 300 micro-entrepreneurs in Enugu both rural and urban, the study demonstrates that digital marketplaces lead to a 40 percent average level of primary revenue growth and broadly increase customer base by as much as 60 percent. Even then, the adoption cannot be complete due to such problems as insufficient digital literacy, high-platform costs, and unstable internet connectivity. The study will fill research gaps in the locality as it will offer more Enugu specific knowledge compared to the wider Nigerian literature. Among the suggestions will be customized digital training, the subsidization of platform access, and investments in infrastructure so as to have the best out of it. This paper highlights the strategic nature of digital marketplace and how it can lead to inclusive economic development of micro-entrepreneurs in Enugu.